Spaza Shops and Community Resilience in Post-Pandemic South Africa: A Sustainable Livelihoods Framework Analysis - Gavaza, Bramwell Kundishora; Fihla, Siphenathi; Manquma, Nangamso (Journal of Cultural Analysis and Social Change, 2025)
The study explores the socioeconomic role of spaza shops in South African communities during the post-COVID-19 period, using the Sustainable Livelihoods Framework as an analytical lens. Spaza shops are embedded within township economies and emerged as critical lifelines during the pandemic, offering proximity-based access to essential goods, informal credit, and social support. The study employed a qualitative research approach, involving interviews with 25 participants. The study's findings reveal that spaza shops serve as both economic and social infrastructure, with their embeddedness in community networks enhancing trust and adaptability. However, challenges such as supply chain fragility, competition from formal retailers, and policy pressures surrounding formalisation threaten their sustainability. The study argues for calibrated policy interventions that preserve the accessibility and resilience of spaza shops while promoting accountability and safety. By situating spaza shops within the SLF, the research contributes to broader debates on informal economies, inclusive development, and post-pandemic recovery strategies in South Africa.